2015
DOI: 10.5812/archcid.22540
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CTX-M, TEM and SHV Beta-lactamases in Clinical Isolates of Escherichia Coli and Klebsiella Pneumoniae Isolated From Aleppo University Hospitals, Aleppo, Syria

Abstract: Background: Extended spectrum β-lactamases (ESBLs) have emerged as a major threat worldwide, with limited treatment options available. Objectives: The present study aimed to estimate the prevalence, possible types of ESBL genes and antibiotic resistant patterns of ESBLproducing Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae). Materials and Methods: A total of 199 clinical isolates of E. coli and K. pneumoniae, collected between October 2010 to March 2012, at three University Hospitals in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
(49 reference statements)
5
19
2
Order By: Relevance
“…In this study, bla CTX -M (64.5%) was found in the majority of ESBL-producing K. pneumoniae isolates, followed by bla SHV (54.8%) and bla TEM (41.9%). In agreement with the present study, AL-Subol and Youssef found that bla CTX -M was the most prevalent among E. coli and K. pneumoniae isolates in Syria, followed by bla SHV and bla TEM (38). The findings of the present study are consistent with an earlier study conducted in Morocco which found that CTX-M enzymes were the most common ESBL types (39).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, bla CTX -M (64.5%) was found in the majority of ESBL-producing K. pneumoniae isolates, followed by bla SHV (54.8%) and bla TEM (41.9%). In agreement with the present study, AL-Subol and Youssef found that bla CTX -M was the most prevalent among E. coli and K. pneumoniae isolates in Syria, followed by bla SHV and bla TEM (38). The findings of the present study are consistent with an earlier study conducted in Morocco which found that CTX-M enzymes were the most common ESBL types (39).…”
Section: Discussionsupporting
confidence: 93%
“…The dramatic shifts reported in the types of ESBLs from Europe, Asia, and South America, with strains producing CTX-M becoming dominant (19,21,24,25). The urinary ESBL E. coli and K. pneumoniae isolates in this study were carried high rate of bla CTX-M gene (46.7% and 22.8%, respectively) and bla TEM genes (30% and 27.5%, respectively).…”
Section: Discussionmentioning
confidence: 89%
“…Surveillance data reported various levels of ESBL-producing strains of K. pneumoniae and E. coli throughout the world. The ESBL rates in northern Europe, north America, and Australia is 5%-10%, in contrast, high level ESBL producer K. pneumoniae and E. coli were found in Syria (≥ 60%), India (≥ 80%), China (≥ 60%), and other areas in east and southeast Asia, southern Europe (≥ 30%) (21,22,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, these contrast with Saha et al, [23] ESBL producers were observed among Klebsiella spp. (75%) and with AL-Subol and Youssef, [24] they were detected (67.5%) of K. pneumoniae, different rates for the prevalence of ESBL-producing K. pneumoniae are detecting in the variation difficult to explain but may be due to differences in antibiotic exhaustion and a variety of specimens handling time. Further, E. coli isolates was resistant to the antimicrobial agents meropenem, ceftazidime, cefoxitin, ceftriaxone, aztreonam, and cefoxitin with percentage of resistance 16.7%, 83.3, 83.3%, 100%, and 100, respectively.…”
Section: Discussionmentioning
confidence: 92%